Konsep Pembaharuan Pendidikan Di Indonesia Perspektif Harun Nasution dan Nurcholish Madjid - Norafiza, Sri; Nur’aina, Nur’aina; Harahap, Nasrun (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Islamic education is an activity carried out consciously and in a planned way by developing, improving, leading, training, nurturing students so that they can actively develop the potential that exists within them with the aim of having religious spiritual strength, knowledge, noble morals and the skills needed to live life in this world and towards the afterlife in accordance with Islamic values. Thoughts on Islamic education have always been a hot topic of conversation from time to time. Starting from the emergence of Islam as a religion to the elaboration of Islam, it became an object of study in the realm of thought by Muslim scholars and orientalists. The aim of this research is to see the views of two figures, Harun Nasution and Nurcholish Madjid, who were figures in the development of Islamic thought who were quite influential in their time. This research method is included in library research. The research results show that both education systems are based on the principles of the Koran which emphasizes the importance of morals and the need for education in all aspects of life.